Navigating works future: Harnessing digital innovation to enhance muslim employees performance through transformation and flexibility - Usep Deden Suherman; Ateng Kusnandar; Husni Rofiq; Suteja Wira Dana Kusuma (Universitas Islam Malang, 2025)
Fierce competition and uneven quality of service have made higher education institutions face pressure to undergo digital transformation and increase human resource performance. These challenges show that the implementation of digital transformation and organisational flexibility is not fully optimal, especially when digital innovation is not developed as a primary capability. Although many studies specifically examine digital transformation and organisational flexibility, studies specifically examining how digital innovation plays a unique mediator role in strengthening employees’ performance are still limited. This research fills the gap that has not been much explored. Using the explanation survey methods, 250 respondents were obtained from several educational institution units. The results indicate that digital transformation has a positive effect and a significant impact on digital innovation. Besides that, organisational flexibility is directly linked to increased employee performance. Most importantly, digital innovation plays a crucial role as a full mediator, distributing the effects of digital transformation and enhancing organisational flexibility, thereby improving the impact on employees’ performance. These findings confirm that technological transformation and organizational flexibility are sustainable performance advantages.